A method for eliminating bacterial contamination from in vitro moss cultures1. (5th January 2015) - Carey, Sarah B.; Payton, Adam C.; McDaniel, Stuart F.
Abstract : Premise of the study: Bacterial contamination is a major problem in plant tissue culture, resulting in loss of experimental strains or preventing use of field‐collected isolates. Here we evaluated an agar embedding method for eliminating bacteria from experimental cultures of the mosses Ceratodon purpureus and Physcomitrella patens . Methods and Results: We blended moss protonema that had been inoculated with bacteria and embedded the cell fragments in antibiotic‐containing, low‐concentration agar. The plants were placed in a growth chamber and allowed to grow until the moss grew out of the media. The plants were then transferred to new plates and observed for contamination. The embedding method consistently outperformed standard procedures. Conclusions: The embedding method places moss in direct contact with antibiotics, arresting bacterial replication and allowing moss to outgrow contamination. We anticipate this method will prove valuable for other plants capable of clonal propagation by blending.